The Effect of Context in Words Substitution of Qur’anic Expression-Samples from the Rhetorical Study by Al Samarrai- - عصمان , نسيم (Milev Journal of Research and Studies, 2023)
This study came to look for one of the rhetorical interpretation issues in Qur’an by Doctor Fadel Al-Samarrai which is called substituting words in the Qur’anic expression. We deal with a lot of Qur’anic verses that are very similar in their subjects and words especially verses that tell us stories of the previous ones. Then, a difference comes to you in a word or two words. This thing draws attention and makes the researcher excited to know the secret of this substitution. The study revealed that the context has a big role in substituting these words in the Qur’anic stories